Effectiveness of Climate Resilient Interventions on Performance of Dairy Animals in Karnal District of Haryana - Yadav, Pushpendra; Meena, B. S.; Saurav, Subhash Kumar; Pavan, Parjanya; Barman, Bikram; J. Anu; Bishnoi, Sitaram (Indian Journal of Extension Education, 2025)
To promote climate-resilient agriculture, the Indian Council of Agricultural Research (ICAR) initiated the National Innovations in Climate Resilient Agriculture (NICRA) project. In light of this context, the current study was undertaken in 2022 to assess the effectiveness of technological interventions on the reproductive and productive performance of dairy animals. This study was conducted in the Karnal district of Haryana, which was selected purposively. A sample of 120 respondents was selected, comprising 60 individuals from three NICRA beneficiary villages and 60 from three non-beneficiary villages. Using the Mann-Whitney U test, a significant difference was observed in the productive and reproductive performance of dairy animals. In the beneficiary villages, indigenous cows showed an improvement in both average daily milk yield and lactation yield. Among crossbred cows, there was a positive increase in average daily milk yield, peak yield, lactation yield, and lactation length. Similarly, buffaloes owned by beneficiary farmers exhibited enhanced peak yield, daily milk production, and overall lactation yield. Correlation of socio-economic variables like family education, experience, and participation in extension activities showed a positive correlation towards the productive parameters and a negative correlation towards inefficiencies of reproductive parameters, indicating their enhancing influence on dairy animals.